The construct of identity in Hellenistic Judaism: essays on early Jewish literature and history - Gruen, Erich S. (Deuterocanonical and cognate literature studies, 2016)
This book collects twenty two previously published essays and one new one by Erich S. Gruen who has written extensively on the literature and history of early Judaism and the experience of the Jews in the Greco-Roman world. His many articles on this subject have, however, appeared mostly in conference volumes and Festschriften, and have therefore not had wide circulation. By putting them together in a single work, this will bring the essays to the attention of a much broader scholarly readership and make them more readily available to students in the fields of ancient history and early Judaism. The pieces are quite varied, but develop a number of connected and related themes: Jewish identity in the pagan world, the literary representations by Jews and pagans of one another, the interconnections of Hellenism and Judaism, and the Jewish experience under Hellenistic monarchies and the Roman empire.